2008
DOI: 10.1104/pp.108.124354
|View full text |Cite
|
Sign up to set email alerts
|

Independently Silencing Two Photosynthetic Proteins inNicotiana attenuataHas Different Effects on Herbivore Resistance  

Abstract: Insect attack frequently down-regulates photosynthetic proteins. To understand how this influences the plant-insect interaction, we transformed Nicotiana attenuata to independently silence ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBPCase) activase (RCA) and RuBPCase and selected lines whose photosynthetic capacity was similarly reduced. Decreases in plant growth mirrored the decreases in photosynthesis, but the effects on herbivore performance differed. Both generalist (Spodoptera littoralis) and spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
70
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 56 publications
5
70
0
Order By: Relevance
“…Consistent with our data, it has been reported that the tobacco (Nicotiana tabacum) RCA gene was involved in herbivore resistance (Giri et al, 2006;Mitra and Baldwin, 2008). The tobacco RCA was decreased at the levels of transcript and protein abundance by herbivore damage (Giri et al, 2006).…”
Section: Mutation In Rca Led To Typical Senescence-associated Featuressupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our data, it has been reported that the tobacco (Nicotiana tabacum) RCA gene was involved in herbivore resistance (Giri et al, 2006;Mitra and Baldwin, 2008). The tobacco RCA was decreased at the levels of transcript and protein abundance by herbivore damage (Giri et al, 2006).…”
Section: Mutation In Rca Led To Typical Senescence-associated Featuressupporting
confidence: 92%
“…The tobacco RCA was decreased at the levels of transcript and protein abundance by herbivore damage (Giri et al, 2006). Furthermore, down-regulation of this RCA gene caused reduced defense against herbivore attack (Mitra and Baldwin, 2008).…”
Section: Mutation In Rca Led To Typical Senescence-associated Featuresmentioning
confidence: 99%
“…[15][16][17][18][19][20][21] The rca-1 and rca-2 mutants displayed obviously decrease in the JA-induced expression of two defense-responsive genes plant defensin 1.2 (PDF1.2) and thionin 2.1 (Thi2.1), 5,22,23 suggesting that RCA may also play a role in JA-mediated defense responses. The multi-function of RCA in defense responses indicates that there might be some common elements in these processes, which is worthy to be identified.…”
mentioning
confidence: 99%
“…Silencing of these genes improved the performance of a native generalist (Spodoptera littoralis) and specialist (Manduca sexta) herbivorous larvae on transformed host plants (Mitra & Baldwin, 2008). Similarly, it was shown that independent silencing of the TMP 14 kDa thylakoid membrane phosphoprotein, PSI P700 apoprotein, and Fructose-1,6-bisphosphatase in near-isogenic (NILs) Triticum aestivum lines using VIGS, also affected host resistance to Diuraphis noxia in varying degrees (Jackson, 2010).…”
Section: Linking Photosynthesis and Plant Defencementioning
confidence: 99%
“…The linkage between photosynthesis and host defence was recently demonstrated by silencing two central photosynthetic proteins, i.e., ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) and Rubisco activase in Nicotiana attenuata using virusinduced gene silencing (VIGS) (Mitra & Baldwin, 2008). Silencing of these genes improved the performance of a native generalist (Spodoptera littoralis) and specialist (Manduca sexta) herbivorous larvae on transformed host plants (Mitra & Baldwin, 2008).…”
Section: Linking Photosynthesis and Plant Defencementioning
confidence: 99%